MODERN ASPECTS OF MULTIMODAL TRANSPORTATION - Хара, Марина; Регуш, Владимир; В, совете (SWorldJournal, 2020)
Ukraine has a great transit potential, its implementation requires the use of all opportunities provided by multimodal transportation and modern digital technologies, so the issue of multimodal transportation for Ukraine is a topical issue and extremely i